A comparative study of hydroxyethylcellulose‐based solid polymer electrolytes for solid state Zn batteries. Issue 1 (10th December 2022) - Brige, Amandine; Olsson, Martina; Xiong, Shizhao; Matic, Aleksandar
Abstract: Rechargeable zinc metal batteries are greener and safer alternative to lithium batteries, but they suffer from poor reversibility due to growth of zinc dendrites and water splitting reactions of aqueous electrolytes. One strategy to overcome these drawbacks is replacing aqueous electrolyte with solid polymer electrolyte (SPE). In this work, we examine the possibility of fabricating solid electrolyte from a bio‐based polymer, hydroxyethylcellulose (HEC), with the aim to further increase the sustainability of zinc batteries. Various types of zinc salts, drying procedures and the salt concentrations are investigated for their impact on the ionic conductivity, structure, and phase behavior of as‐prepared polymer electrolytes. It is found that HEC has a good film‐forming ability compared with commonly used poly(ethylene oxide) but its low salt‐dissociation capability leads to an ionic conductivity of 10 −6 S cm −1 even at the elevated temperature of 110°C, hindering the possibility of solely utilizing HEC as matrix of solid electrolyte. Our results suggest that introducing a new polymer with higher salt‐dissociation capability or lower glass transition temperature into the HEC matrix can be a reliable way to build solid polymer electrolytes with sufficient ionic conductivity and good mechanical property for future zinc batteries. Abstract : Fabrication of polymer electrolytes from hydroxyethylcellulose (HEC) is explored in this work for zinc batteries. Selection of key components, polymer matrix and zinc salt, is systematically examined by mechanical property, ionic conductivity, and local structures. Our results show that HEC presents a good film‐forming ability, but its low salt‐dissociation capability leads to a low ionic conductivity.